Muscle growth/strength versus endurance signal transduction pathways and their interaction - Wackerhage, H. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
In many sports athletes need to train for both strength/muscle mass and endurance. Equally muscle mass/high strength and high endurance are associated with health and longevity. This provides a rationale for athletes and fitness-orientated exercisers to increase strength/muscle mass and endurance at the same time. The aim of this presentation is to introduce a) a general theory of adaptation to exercise, b) to introduce the signal transduction pathways that mediate skeletal muscle growth and endurance adaptations in response to specific types of exercise and c) to highlight the interaction between these pathways. Key muscle growth pathways are the mTOR and Smad pathways whilst endurance adaptations are regulated by the AMPK/CaMK-PGC-1á and calcineurin NFAT pathways. These evolutionary highly conserved pathways also interact with each other and there is the evidence for circadian behaviour